Which CEO Characteristics and Abilities Matter? - KAPLAN, STEVEN N.; KLEBANOV, MARK M.; SORENSEN, MORTEN (Journal of Finance, 2012)
ABSTRACT We exploit a unique data set to study individual characteristics of CEO candidates for companies involved in buyout and venture capital transactions and relate these characteristics to subsequent corporate performance. CEO candidates vary along two primary dimensions: one that captures general ability and another that contrasts communication and interpersonal skills with execution skills. We find that subsequent performance is positively related to general ability and execution skills. The findings expand our view of CEO characteristics and types relative to previous studies.